Trace metals in core sediments from a deep lake in eastern Turkey: Vertical concentration profiles, eco-environmental risks and possible sources - Varol, Memet; Canpolat, Ozgur; Eris, Kursad Kadir; Caglar, Metin (Academic Press Inc Elsevier Science, 2020)
The contents of 12 trace metals (Hg, As, Pb, Cd, Ni, Cr, Zn, Cu, Co, Mn, Al and Fe) in two sediment cores (Hz11-P02 and Hz11-P09) from the Lake Hazar, one of the deepest natural lakes in Turkey, were examined to evaluate vertical concentration profiles, possible sources, pollution status and eco-environmental risks of these metals. The highest concentrations of Cd and As were detected in the upper part (0-10 cm depths) of core Hz11-P02, while Hg concentration was at a maximum in the upper part of core Hz11-P09. The concentrations of other metals except Cr were the highest in the bottom layer (depths below 100 cm) of both cores. Among trace metals (TMs), Cr, Ni, Al and Mn in core Hz11-P02 and Mn in core Hz11-P09 showed statistically significant correlations with core depth (p < 0.01). The mean concentrations of Hg, Pb, Cd, Cu, Zn, Co, Mn, Al and Fe in core Hz11-P02 were significantly higher than those in core Hz11-P09 (p < 0.01). Also, the mean enrichment factor, geoaccumulation index and contamination factor values of As, Cu, Cd, Zn, Pb and Hg were higher in core Hz11-P02. The ecological risk index (RI) values for core Hz11-P02 were between 150 and 300 in 40.3% of the samples, indicating moderate ecological risk, whereas the RI values for core Hz11-P09 were < 150 in 100% of the samples, indicating low ecological risk. Factor, cluster and correlation analyses, and contamination indices indicated that As and Hg in core Hz11-P02 predominantly originated from anthropogenic sources, while 12 trace metals in core Hz11-P09 derived from natural sources.
Keywords: Trace metals; Lake hazar; Sediment core; Source identification; Eco-environmental risks